2013
DOI: 10.1111/and.12159
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin attenuates carbon tetrachloride-induced testicular damage in rats

Abstract: This study was conducted to investigate the effect of quercetin on carbon tetrachloride (CCl4 )-induced sperm damages, testicular apoptosis and oxidative stress in male rats. Group 1 served as control, group 2 was treated with only quercetin, group 3 was treated with only CCl4 and group 4 received CCl4 + quercetin. All administrations were performed by gavage and maintained for 10 weeks. CCl4 administration caused significant decreases in absolute and relative reproductive organ weights, sperm motility, concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…This result agrees with Sonmez et al (2014). Additionally, results revealed that abnormalities such as amorphous and without hook were the most frequently observed types after CCL4 exposure which coincides with Abdou, Salah, Hoda, and Abdel Rahim (2012).…”
Section: Resultssupporting
confidence: 89%
“…This result agrees with Sonmez et al (2014). Additionally, results revealed that abnormalities such as amorphous and without hook were the most frequently observed types after CCL4 exposure which coincides with Abdou, Salah, Hoda, and Abdel Rahim (2012).…”
Section: Resultssupporting
confidence: 89%
“…Thus quercetin showed cytoprotection due to its effect on prevention of free radical production in testicular cells, so mechanical disruption of epithelium was less. These findings were supported by previous studies demonstrating that active compounds present in quercetin has protective effects against testicular damage caused by different toxic agents such as carbon tetrachloride (Sonmez et al, 2014), docetaxel (Altintas et al, 2015), TCDD (Ciftci et al, 2012) and FNT (Saber et al, 2015).…”
Section: Ultra Structuresupporting
confidence: 85%
“…This study used probably young animals (unknown age, an average body weight of 131 g was reported) and applied only a relatively low quercetin dose . Other studies with adults male rats, investigating primarily beneficial effects of quercetin against chemically induced reproductive toxicity, did not find any deleterious effects on sperm parameters, reproductive organ weights, and histopathology or on testicular and plasma testosterone levels after administration of 50 mg quercetin per kg bw per day for 7 or 10 weeks or 150 mg quercetin per kg bw per day for 10 weeks …”
Section: Safety Aspectsmentioning
confidence: 99%